2018
DOI: 10.1215/03616878-7104392
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Content of Television Health Insurance Advertising during Three Open Enrollment Periods of the ACA

Abstract: Television advertising has been a primary method for marketing new health plans available under the Affordable Care Act (ACA) to consumers. Kantar Media/CMAG data were used to analyze advertising content during three ACA open enrollment periods (2013-2016). Few advertisement airings featured people who were elderly, disabled, or receiving care in a medical setting, and airings increasingly featured children, young adults and people exercising overtime. The most common informational messages focused on plan cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…As Republicans fight the ACA, we might expect other sponsors to submerge the role (that is, hide mentions) of the ACA in their advertisements. We see indications of this submerging in data from the first three open enrollment periods, where 49 percent of ads mentioned the ACA in the first open enrollment period but only 31 percent in the second and third (Barry et al 2018). There is likely an interaction between different types of communication, with the political communication strategies shaping insurer strategies, and vice versa.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…As Republicans fight the ACA, we might expect other sponsors to submerge the role (that is, hide mentions) of the ACA in their advertisements. We see indications of this submerging in data from the first three open enrollment periods, where 49 percent of ads mentioned the ACA in the first open enrollment period but only 31 percent in the second and third (Barry et al 2018). There is likely an interaction between different types of communication, with the political communication strategies shaping insurer strategies, and vice versa.…”
Section: Discussionmentioning
confidence: 90%
“…This decline in reported exposure, despite the high volumes of private advertising (as noted in figure 4), may indicate that consumers did not perceive the increased presence of private advertising as a share of all health insurance ads as providing ACA-specific information as much as government-sponsored ads do. Indeed, references to the ACA in all insurance ads aired declined between 2013 and 2016 (Barry et al 2018) and in insurance-company sponsored ads in particular .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data have been used in previous studies examining advertising in health care. 3,9,19 Designated market areas consist of groups of counties surrounding metropolitan areas and were developed by Nielsen Holdings (a data and market measurement company) to track television viewership. Media advertising is typically purchased at the DMA level.…”
Section: Sources Of Data and Study Populationmentioning
confidence: 99%
“…As messages that confronted consumers varied significantly regionally, advertising and news coverage potentially affected perception of the rollout of the ACA early on. Interestingly, research has also shown that the political content during open enrollment seasons declined significantly over time, as insurers began to focus more on the promotion of enrollment and plan benefits, for example (Barry et al, ).…”
Section: Substantive and Theoretical Issues Coveredmentioning
confidence: 99%